Alcohol‐attributable healthcare attendances up to 10 years prior to diagnosis of alcoholic cirrhosis: a population based case–control study. (29th December 2015) - Otete, Harmony E.; Orton, Elizabeth; Fleming, Kate M.; West, Joe
Abstract: Background & Aims: Cirrhosis because of alcohol could be avoided if drinking behaviour could be altered earlier in the disease course. Our aim was to quantify the burden of morbidities in patients prior to alcoholic cirrhosis diagnosis, as this may inform the earlier identification of people at high risk for targeted interventions. Methods: We carried out a case–control study using 2479 incident cases of alcoholic cirrhosis and 24 790 controls identified from 357 primary and secondary care centres in England. We assessed the prevalence of morbidities that are partly attributable to alcohol (namely malignant neoplasms, diabetes, epilepsy, injuries, cardiovascular and digestive diseases) prior to alcoholic cirrhosis diagnosis. We compared prevalence in cases to the control population and used logistic regression to derive odds ratios (95% CI). Results: Fifty‐eight per cent of cases compared to 29% of controls had had at least one alcohol‐attributable condition before cirrhosis diagnosis. The most frequent conditions (proportion in cases vs. controls) were intentional injuries (35.9% vs. 11.9%) and cardiovascular diseases (23.2% vs. 15.6%), followed by diabetes (12.8% vs. 5.3%), digestive diseases (6.1% vs. 1.2%) and epilepsy (5.0% vs. 1.1%). The strongest association with alcoholic cirrhosis was found for digestive diseases [OR 5.4 (4.4–6.7)], epilepsy [OR: 4.4 (3.5–5.5)] and injuries [OR: 4.0 (3.7–4.4)] particularly among those aged 18–44 years. Conclusion: These data highlight the high burden of other alcohol‐attributable conditions in patients prior to alcoholic cirrhosis diagnosis. Reviewing those consistently presenting with any of these conditions more closely could help practitioners reduce/avoid the long‐term consequences of development of alcoholic liver disease.